What is the lifetime cost of alcohol consumption? an estimation of economic burden in Thailand - Chaisiri Luangsinsiri; Montarat Thavorncharoensap; Usa Chaikledkaew; Oraluck Pattanaprateep; Naiyana Praditsitthikorn; Bundit Sornpaisarn; Jürgen Rehm (PLoS ONE, 2025)
This study aimed to estimate the lifetime cost of alcohol consumption per individual drinker in Thailand to support policy formulation. Using an incidence-based cost-of-illness (COI) approach, a hybrid model combining a decision tree and a Markov model, incorporating six major alcohol-related diseases and conditions (i.e., hypertension, hemorrhagic stroke, liver cirrhosis, liver cancer, alcohol use disorders, and road injuries), was employed to analyze both direct costs (i.e., direct medical, direct nonmedical, property damage) and indirect costs (i.e., absenteeism, premature mortality). All costs were reported in Thai baht 2022 (35.06 THB = 1US$). From a societal perspective, the lifetime costs for individual male and female drinker were estimated at 721,344 THB (95% CI: 687,910–754,779) and 263,812 THB (95% CI: 249,250–278,374), respectively. Quitting earlier reduced costs significantly, with average quitting ages resulting in the cost of 568,932 THB for males and 115,167 THB for females. On average, each Thai drinker incurs a cost of 498,196 THB. These findings highlight the substantial economic burden of alcohol consumption in Thailand, underscoring the critical need for effective interventions and policies, along with more rigorous enforcement of current regulations aimed at encouraging early cessation and preventing the initiation of drinking, such as through advertising bans, sales restrictions, improving access to counseling and treatment.